Beyond its mineral/natural resource : why Africa matters to the world - Ibrahim A. Gambari (2014)
After independence, many African states assumed self-governance would produce good governance, but the experience proved otherwise with military coups, civil wars, poor trade relations, external debt and famines. These problems resulted in a sense of “Afro-pessimism.” However, after the end of the Cold War, a new phase of political maturity led to high growth in Africa and improving development indicators, resulting in a period of “Afro-enthusiasm” with African contributions to the global system increasing. However multiple challenges remain that could threaten the progress already achieved. This paper examines several of these challenges but also opportunities that arise in tackling them, particularly on-going conflicts, economic inequality and poverty, new centres of gravity of world religions, climate change, demographic changes, the youth and unemployment, gender disparities, food insecurity, and weak governance systems. African leaders are cognisant of these challenges and have created important structures aimed at addressing these challenges. As this paper argues, the crux is the need for further progress in improving political and economic governance in Africa. The most important of these are regional initiatives: The Comprehensive Africa Agricultural Development Programme (CAADP) aims to eliminate hunger and reduce poverty. The New Partnership for African Development (NEPAD) is aimed at tackling governance issues in development and includes the voluntary African Peer Review Mechanism (APRM) that allows countries to undergo review of their reforms by other participating states. The African Union (AU) Constitutive Act prohibits the takeover of power by unconstitutional means, and has real powers to punish members that undergo military coups. These initiatives are markers of progress that will allow Africa to enter a new period where opportunities are recognised albeit with a realistic view of the difficulties Africa still faces as it grows. The importance of building peace, sustaining economic growth and providing conducive environments for investment are recognised, and will make Africa a significant region in global affairs.